A COMPARATIVE SEMANTIC ANALYSIS OF PRAISE EXPRESSIONS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2026)
This article provides a comprehensive comparative semantic analysis of praise expressions in English and Uzbek from the perspective of functional semantics. Praise is examined as a category of positive evaluation that reflects linguistic, cultural, and communicative values. The study aims to identify the semantic structure of praise expressions, distinguish their core and peripheral components, and reveal similarities and differences between the two languages. The research employs comparative, componential, and contextual analysis of lexical and phraseological units. The findings demonstrate that although English and Uzbek praise expressions share universal evaluative features, they differ in cultural motivation, intensity, and functional orientation, highlighting the influence of language-specific and socio-cultural factors.